ANALISIS KEBUTUHAN TERMINAL PENUMPANG PELABUHAN PENYEBERANGAN KEWAPANTE - Silvano Karlitos Meko; Dedi Imanuel Pau; Alfrendo Satriawan Kabupung (Program Studi Teknik Sipil, 2024)
The Kewapante Ferry Port, located in Maumere City, Sikka Regency, is a seaport that plays an important role in inter-regional sea transportation traffic in Sikka Regency. Starting from the need for sufficient and sufficient port facilities, this research was conducted to study or analyze the capacity of the Kewapante Ferry Port Passenger Terminal. This research was carried out by collecting and analyzing data from the relevant agencies for the last 5 years (2016 to 2020), as well as data on the area and layout of the research location. This research uses a simple linear regression method to predict or forecast passenger flows based on 2016-2020 data, and then analyze the need for facilities or space at port terminals for the next few years. Based on the results of the passenger terminal demand analysis, it can be predicted that the overall demand in 2021 will be 842 m2, in 2022 it will be 772 m2, in 2023 it will be 703 m2, in 2024 it will be 631 m2 and in 2025 it will be 561 m2. From the results of this analysis, it is possible to develop facilities at port terminals that are still inadequate or do not meet existing needs.